Characteristics and consequences of families with low levels of financial wealth - Bee Boileau; Jonathan Cribb; Thomas Wernham (Institute for Fiscal Studies (IFS), 2023)
Many families have little or no savings to access on a 'rainy day'. We examine the types of families with low savings and what the consequences are.
Keywords: 330; Savings; pensions and wealth; Distributional effects; Family; Inequality; Living standards; Savings; Wealth